OPTIMASI SABUN CAIR ANTIBAKTERI EKSTRAK ETANOL RIMPANG JAHE MERAH (Zingiber officinale Rosc. var. rubrum) VARIASI VIRGIN COCONUT OIL (VCO) DAN KALIUM HIDROKSIDA (KOH) MENGGUNAKAN SIMPLEX LATTICE DESIGN - ., Haris Fadillah (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Antibacterial liquid soap help prevent the infection of pathogenic bacteria, such as S. aureusand E. coli that can cause skin infection and diarrhea. Red ginger is one of natural plants that hasthe potential as an antibacterial agent in soaps and also known to have antibacterial activity. Soap isformed from the reaction between a fattty acid and base so its quality is affected by the perfection ofthat reaction. The purpose of this study was to determine the optimum composition of VCO andKOH using Simplex Lattice Design (SLD) and its physicochemical properties. The extraction wasdone by soxletation method using ethanol 96%. Antibacterial test showed that the optimumconcentration of the extract was 50 mg/mL. Soap with variation of the VCO and KOH had specificgravity 0,955-1,045; viscosity 0,3-2,1; pH 9,366-10,566; and free alkali 7,48x10%.The composition of the VCO and KOH that predicted by SLD is 26,386 g VCO and 6,414 g KOH.This optimum formula had specific gravity 1.03148; viscosity 0.723; pH 10,066; and 0.0086% freealkali. Independent two-sample test between the physicochemical properties resulted from the testand results predicted by SLD showed no significant difference (p>0,05). The antibacterial activityof optimum formula didnâ€™t differ significantly with the control (p>0,05). Keywords:Â  liquid soap, red ginger, virgin coconut oil, potassium hydroxide, simplex lattice design